THE EFFECT OF AMYLUM ADHESIVE AND SAWDUST COMPOSITION FOR RUBBER SEED SHELL BIO-BRIQUETTE AS AN ENVIRONMENTALLY FRIENDLY ALTERNATIVE FUEL - Fathia Eka Pratiwi; Pitri Yenica; Maulidia Putri (Jurnal PPI Dunia, 2018)
The purpose of this reaserch is to determine the optimum composition of rubber seed shell, sawdust,and amylum adhesive. Experiments were carried out in several stages: aggregate of the raw materials,drain the raw materials, do carbonization or combustion with 600°C temperature for 2 hours, restrict thesupply of oxygen so that the materials do not burn to ashes, sieve the materials, weigh each ofingredients in the ratio of 60:20:20, 50:20:30, 40:20:40, and 30:20:50, blend the materials, print thebriquettes, drain, and analyze the contents of briquette. This reasearch generates optimumcompositionwith ratioof 60% rubber seed shells, 20% sawdust and 2 % amylum adhesive. It is in termsof the parameters that have been analyzed in the form of spesification of inherent moisture is 4.99%,ash content is 4.38%, volatile matter content is 24.75%, fixed carbon is 66.38% and calorific value is6069 cal/gr.